Sejarah Perlindungan Anak Dalam Perkembangan Hukum Internasional dan Hukum Nasional Indonesia - Indra Pratama; Faisar Ananda (Scientific Journal for Nation Building, 2026)
Child protection constitutes an integral part of the human rights system and has undergone significant development in response to social, political, and legal transformations across various countries. In the early development of legal systems, children were primarily regarded as objects under the authority of the family and had not yet been recognized as independent rights holders. As global awareness of the need to protect vulnerable groups increased, various international legal instruments began to regulate children's rights specifically. This study aims to examine the historical development of child protection in international law and Indonesian national law, as well as to analyze the paradigm shift in the concept of child protection. The research employs a normative legal method using both historical and statutory approaches. The findings indicate that the development of child protection at the international level began with the Geneva Declaration of the Rights of the Child (1924), continued through the Declaration of the Rights of the Child (1959), and reached a more comprehensive framework with the Convention on the Rights of the Child (1989). In Indonesia, the evolution of child protection has been marked by the strengthening of constitutional guarantees, the ratification of the Convention on the Rights of the Child through Presidential Decree No. 36 of 1990, and the enactment of various laws and regulations specifically governing children's rights and legal protection. These developments demonstrate a fundamental paradigm shift from a welfare-based approach to a rights-based approach that recognizes children as legal subjects possessing rights that must be respected, protected, and fulfilled.